Ivan Ayanov as “Matchless Leporello” (Concerning the subject of Don Juan in I.A. Goncharov’s novel “The Precipice”) (Proceedings of Southern Federal University. Philology, 2015)
On the basis of the analysis of the first journal publications “Sophia Nikolaevna Belovodova” (1860), “Portrait” (1861) and manuscript editions of the novel “The Precipice” by I.A. Goncharov, the article traces the development of image of I.I. Ayanov associated with the formation of the final novel writer Don Juan theme. In the result of the study, it was found that the Don Juan theme in the novel has undergone some transformation from virtually dashed references in journal publications, through the gradual inclusion in chapters manuscript editions of the first part of the novel, to turn it into one of the leading themes in the novel “The Precipice”.Keywords: history of the novel “The Precipice”, Don Juan theme, image of I.I. Ayanov.Retsov Vasily Vyacheslavovitch - postgraduate student of Russian literature department of the Institute of Philology, Journalism and CrossCultural Communication, Southern Federal University. Е-mail: goustking@ yandex.ru